2022
DOI: 10.1088/1755-1315/1037/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Influence factors of clearance leakage flowrate and clearance hydraulic axial force of pump-turbine

Abstract: The clearance flow of pump-turbine has significant influence on hydraulic forces of the runner, which is related to safety of the unit. To clarify the influence factors, clearance flowrate and clearance hydraulic axial force of a prototype pump-turbine were analyzed by 3D CFD simulations. The results show that the rotational speed, and the smallest radial sizes of clearance inlet, outlet, and the seal ring sizes are the determinant factors for clearance leakage flowrate, while the rotational speed and the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We numerically simulated the pressure distributions of the clearance channel with different clearance heights for a pump turbine and found that the clearance height is not sensitive to the clearance pressure distribution (Hou et al, 2021a). Therefore, the clearance height has little effect on the pressure distribution in the clearance cavity of the pump turbine if the location is far from the boundary effect.…”
Section: Pressure Distributionsmentioning
confidence: 99%
“…We numerically simulated the pressure distributions of the clearance channel with different clearance heights for a pump turbine and found that the clearance height is not sensitive to the clearance pressure distribution (Hou et al, 2021a). Therefore, the clearance height has little effect on the pressure distribution in the clearance cavity of the pump turbine if the location is far from the boundary effect.…”
Section: Pressure Distributionsmentioning
confidence: 99%